Human-biting activities of Anopheles species in south-central Ethiopia. Issue 1 (December 2016) - Kenea, Oljira; Balkew, Meshesha; Tekie, Habte; Gebre-Michael, Teshome; Deressa, Wakgari; Loha, Eskindir; Lindtjørn, Bernt; Overgaard, Hans
Abstract Background Indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) are the key malaria vector control interventions in Ethiopia. The success of these interventions rely on their efficacy to repel or kill indoor feeding and resting mosquitoes. This study was undertaken to monitor human-biting patterns ofAnopheles species in south-central Ethiopia. Methods Human-biting patterns of anophelines were monitored for 40 nights in three houses using human landing catches (HLC) both indoors and outdoors between July and November 2014, in Edo Kontola village, south-central Ethiopia. This time coincides with the major malaria transmission season in Ethiopia, which is usually between September and November. Adult mosquitoes were collected from 19:00 to 06:00 h and identified to species. Comparisons of HLC data were done using incidence rate ratio (IRR) calculated by negative binomial regression. The nocturnal biting activities of eachAnopheles species was expressed as mean number of mosquitoes landing per person per hour. To assess malaria infections inAnopheles mosquitoes the presence ofPlasmodium falciparum andP. vivax circumsporozoite proteins (CSP) were determined by enzyme-linked immunosorbent assay (ELISA). Results Altogether 3, 408 adult female anophelines were collected, 2, 610 (76.6 %) outdoors and 798 (23.4 %) indoors.Anopheles zeimanni was the predominant species (66.5 %) followed byAn. arabiensis (24.8 %), An. pharoensis (6.8 %) andAn. funestus (s.l .) (1.8 %). The overall mean anopheline density was 3.3 times higher outdoors than indoors (65.3vs 19.9/person/night, IRR: 3.3, 95 % CI: 1.1–5.1, P  = 0.001). The mean density ofAn. zeimanni, An. pharoensis andAn. funestus (s.l. ) collected outdoors was significantly higher than indoors for each species (P  < 0.05). However, the meanAn. arabiensis density outdoors was similar to that indoors (11.8vs 9.4/person/night, IRR: 1.3, 95 % CI: 0.8–1.9, P  = 0.335). The mean hourly human-biting density ofAn. arabiensis was greater outdoors than indoors and peaked between 21:00 and 22:00 h. However, An. arabiensis parous population showed high indoor man biting activities during bedtimes (22:00 to 05:00 h) when the local people were indoor and potentially protected by IRS and LLINs. All mosquito samples tested for CSP antigen were found negative to malaria parasites. Conclusions Results show much greater mosquito human-biting activities occurring outdoors than indoors and during early parts of the night, implying higher outdoor malaria transmission potential in the area. However, high bedtime (22:00 to 05:00 h) indoor biting activities of parousAn. arabiensis suggest high potential intervention impact of IRS and LLINs on indoor malaria transmission.